Breast Imaging Review A Quick Guide to Essential Diagnoses - Shah, Biren; Fundaro, Gina.; Mandava, Sabala; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Breast Imaging Review: A Quick Guide to Essential Diagnoses serves as a quick review of essential radiology findings for interpreting multimodality images of the breast. The book includes 92 easy-to-read cases presenting common diagnoses, with over 360 high-quality figures encompassing mammography, ultrasound, MRI, and PET images. Also included are concise pearls covering the basics of interventional breast procedures, such as MRI-guided breast biopsy, galactography, and ultrasound-guided cyst aspirations, along with high yield facts vital to the practice of breast imaging. Co-authored by Drs. Biren A. Shah, Gina M. Fundaro, and Sabala Mandava, this book successfully integrates a comprehensive array of images, diagnoses, and discussion points into a quickly reviewable format. Breast Imaging Review is a valuable resource for radiology residents preparing to take the oral boards, as well as fellows and practicing radiologists interested in reviewing the basics of breast imaging interpretation and interventional procedures.
Part 1. Mammography and Ultrasound Case Review -- Part 2. MRI Case Review -- Part 3. Appendix: I. Interventional Breast Technique Pearls (MRI Wire Localization -- MRI Guided Vacuum Assisted Breast Biopsy -- Ultrasound Guided Core Biopsy -- Ultrasound-Guided Cyst Aspiration -- MRI-Guided Wire Localization -- Galactography) II. High Yield Facts.
Keywords: Medicine; Radiology, Medical; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology